Enantioselective Alkynylation of Aromatic and Aliphatic Aldehydes Catalyzed by Titanium(IV) Complex of D-Glucosamine-derived Sulfonamides - Bauer, Tomasz; Majdecki, Maciej; Smolinskia, Slawomir; Jurczak, Janusz (Current Organic Chemistry, 2014)
We had synthesized a series of β-hydroxy sulfonamides D-glucosamine and applied them as ligands in the titanium tetraisopropoxide-promoted enantioselective addition of phenylacetylene and hexyne-1 to benzaldehyde and selected aromatic and aliphatic aldehydes. The N-3,5-bis(ditrifluoromethyl)benzenesulfonamido-D-glucosamine derivative performed best and we choose it as the most efficient ligand for the addition of phenylacetylene and hexyne-1 to aldehydes. High enantiomeric excesses, up to 96%, were obtained for some aromatic aldehydes.
Keywords: dialkylzinc